Post‐fire regeneration strategies in a frequently burned Cerrado community - Zupo, Talita; Daibes, Luis Felipe; Pausas, Juli G.; Fidelis, Alessandra; Collins, Beverly (Journal of vegetation science, 2021)
Aim Fire is a natural disturbance in many ecosystems throughout the world where plant populations can persist by the resprouting of individuals and/or by recruiting from seeds. We evaluated the post‐fire regeneration response for 41 coexisting species, including grasses, forbs, and shrubs, from an open Cerrado community (campo sujo) in Central Brazil. Location The study was conducted at the Reserva Natural Serra do Tombador (RNST) in Central Brazil. The vegetation of the study area is characterized by a continuous herbaceous layer dominated by grasses and scattered shrubs, which produces fine fuel loads that can burn frequently. Methods We examined both resprouting ability after experimental fires, accounting for bud location, and seed response to heat shocks caused by fire, where seeds were subjected to heat shocks of 100°C for one and three minutes, 200°C for one minute, and a control (untreated seeds). Results All species were able to resprout (R+) after fire, mainly from buds located in underground structures, but also from aerial and basal buds. Seeds of most species tolerated heat shocks of 100°C for one and three minutes, but heat treatments of 200°C decreased seed viability of nearly 50% of species. Seven species, all of which had dormant seeds, showed heat‐stimulated germination. In sum, 81% of the community was classified as R+PT (resprouters with heat‐tolerant propagules) and 17% was R+PS (resprouters with heat‐stimulated propagules). The remaining 2% (one species) was classified as R+P−, showing heat‐sensitive seeds. Conclusions Resprouting is the main post‐fire regeneration strategy in Cerrado open savannas, while fire‐stimulated germination, although possible, is less common in comparison to the frequency in other fire‐prone ecosystems. However, in Cerrado open savannas, heat tolerance is an important trait that enables germination when favorable conditions arise. Fire episode in an open Cerrado community.